Synthesis, characterization, investigation of biological activity, docking studies, and spectroscopic properties of hydrazone compounds containing different substituents - Yilmaz, Engin; Cukurovali, Alaaddin (Canadian Science Publishing, 2019)
To assess electronic absorption spectra, molecular docking, and antibacterial activity, 12 new hydrazone compounds that have different substituents and in different positions were synthesized and characterized. HOMO-LUMO energies and theoretical electronic spectra of synthesized compounds were computed via Gaussian 09 software. Global reactivity descriptors were computed from HOMO-LUMO energies. In addition, 1JXA protein was used for molecular docking studies structure. Staphylococcus aureus ATCC 29213 and Enterococcus faecalis ATCC 29212 (as negative bacteria), Escherichia colt ATCC 25922, and Pseudomonas aeruginosa ATCC 27853 (as gram positive) was selected. Compound 3 was observed to be the most effective against propagations of E. Coll. Similarly, compounds 7 and 9 were found to be the most effective against the reproduction of P. aeroginosa. The most powerful compound against the growth of E. faecalis was ascertained to be compound 7.
Keywords: electronic absorption spectra; hydrazone; antibacterial activity; docking studies; NMR